STRATEGI MEDIA RELATIONS DINAS BINA MARGA PROVINSI RIAU TERKAIT PEMBANGUNAN JEMBATAN SIAK IV - Rahmalia Hernanda; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Siak IV Bridge was built in 2012, to connect access from the downtown area Tassel namely J. Jend. Sudirman. Since the construction of the bridge was halted siak IV arise many questions from the public will be the continuation of the construction of the bridge Siak IV.This research used purposive sampling with criteria informants had experienced in their respective fields over five years, and the number of research subjects as many as five people. The purpose of this study was to determine how to manage the strategy, how to develop strategies, and how to develop a network with the mass media by the Secretariat of the Department of Highways Riau Province Siak IV related to the bridge construction.The results of research in building and maintaining good relationships with journalists is not easy, because they were one of the figures are busy and have an attitude that diverse, but there are some obstacles such as a lack of open communication between the Secretariat Office Binamarga Riau Province and the mass media.Keywords: Media Relations, Pers.